The Ruqyah Syar'iyah Method as an Alternative to Maintaining Family Harmony - Zakman, Arief; Kamaruddin, Kamaruddin; Usman, Ermawati (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
Ruqyah therapy is a sunnah recommended by the Prophet Muhammad. Likewise, in the life of the Prophet Muhammad, doing ruqyah (prayer) for his grandchildren Hasan and Husain was commonplace. The objective of this study is to discuss the Ruqyah method as alternative to mantain families harmony. This study was conducted using qualitative method and the data was gathered through observation, in-depth interview, and written document analysis. The findings of this study show that the Ruqyah Syar'iyyah method applied by the Indonesian Ruqyah Syar'iyyah Association in Palu has met standard operational procedures. The method has three stages: pre-ruqyah, during the ruqyah action, and post-ruqyah. The technique applied by the Ruqyah Syar'iyyah Association in Palu City is following Islamic law or guidance in the Islamic religion. This is seen based on the absence of elements of shirk and haraam in the stages of the process carried out and is seen as very helpful to the community in resolving health problems and household disputes that create disharmony in the family.